PELAKSANAAN PROMOSI PAKET WISATA UMRAH DI PT. AMANAH TRAVEL - Hasikin, Nur; Sulistyani, Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
Umrah is one of the recommended acts of worship in Islam. It is impossible for everyone to be able to travel long distances by themselves, so a guide is needed who can make their pilgrimage easier, namely by using an Umrah travel agency. One of the Umrah travel agents in Pekanbaru is PT. Amanah Travel can make it easier for people to carry out the Umrah pilgrimage without any obstacles. If you want to carry out the Umrah pilgrimage then people can use the available Umrah hajj travel services. PT. Amanah Travel has a permit as an Umrah travel organizer with the RI Kemenang Decree number No. 67/2020. Its strategic location is located at Jl. Pope No. 127D, West Tangkerang Kel, kec. Marpoyan Damai, Pekanbaru City, Riau. This type of research is descriptive qualitative. The research was carried out in June-December 2023. The results of this research were the implementation of promotions for Umrah tour packages at PT. Amanah Travel. The things contained in this research certainly make it easier for people to travel to the holy land so that their worship can be carried out comfortably, safely and without any obstacles. Keywords: Guide, Promotion, Umrah